PENGARUH TEKNIK HOMEWORK BEHAVIORISTIK TERHADAP KEMANDIRIAN SISWA SMP NEGERI 1 BRANG ENE KABUPATEN SUMBAWA BARAT - Yosari, Yessi; Mujiburrahman, Mujiburrahman (Jurnal Paedagogy, 2020)
The purpose of this study was to determine the effect of Behavioristic Homework Techniques on the Independence of Students of SMP Negeri 1 Brang Ene. This research is an experimental study using a one grouf pretest and posttest design. The method used to obtain data in this study was a questionnaire method as the main method. The data analysis used in this research is statistical analysis with the t-test formula. The results of data analysis obtained in this study are the tcount value of 6.957 and the ttable value of 2.056 at a significance level of 5%. Thus there is an effect of behavioristic homework techniques on the independence of students of SMP Negeri 1 Brang Ene, West Sumbawa Regency.